Education and social pedagogy: What relationship?. (1st November 2019) - Moss, Peter; Petrie, Pat
Abstract : This article explores possible relationships between education and social pedagogy. It begins by examining in more detail the theory and practice of social pedagogy, and the profession of social pedagogue widely known in Continental Europe but much less so in the Anglophone world. It then explores some different meanings of education, before considering in more detail the concept of Bildung and its potential for interconnecting education and social pedagogy. It is argued that the relationship between social pedagogy and education depends on the meaning attached to education; and the article ends by considering some implications – for schools, other settings for children and young people, and for their workforces – of choosing a close relationship between education and social pedagogy.